The night we burned : a novel - Kosa, S. F. (Sourcebooks Landmark, 2021)
"When a bizarre murder puts Bend, Oregon in the national media spotlight, Dora Rodriguez, a fact-checker at an online news magazine, heads into town to support the journalist leading the investigation. He's convinced the murder has something to do with the Oracles of Innocence cult massacre that took place in the area twenty years earlier-especially when it's revealed that the victim was a survivor of the still-mysterious catastrophe. Dora is fiercely dedicated to hard facts and accuracy, but when the story veers too close to a past she's desperate to keep hidden, she's forced to bend the truth to protect herself...even as it becomes clear she is already in the killer's sights"--